Thymus antibody-secreting cells: once forgotten but not lost - Pioli, KimAnh Trang; Pioli, Peter Dion (Frontiers in Immunology, 2023)
Antibody-secreting cells are essential contributors to the humoral response. This is due to multiple factors which include: 1) the ability to secrete thousands of antibodies per second, 2) the ability to regulate the immune response and 3) the potential to be long-lived. Not surprisingly, these cells can be found in numerous sites within the body which include organs that directly interface with potential pathogens (e.g., gut) and others that provide long-term survival niches (e.g., bone marrow). Even though antibody-secreting cells were first identified in the thymus of both humans and rodents in the 1960s, if not earlier, only recently has this population begun to be extensively investigated. In this article, we provide an update regarding the current breath of knowledge pertaining to thymus antibody-secreting cells and discuss the potential roles of these cells and their impact on health.